2013
DOI: 10.7863/ultra.32.10.1815
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ultrasound Correlation‐Based Flow Velocity Mapping and Edge Velocity Gradient Measurement

Abstract: he blood flow velocity profile is important for diagnosis of cardiovascular diseases, which are associated with abnormal blood flow in arteries due to hemodynamic changes in patients. 1 The blood flow velocity gradient at the wall edge has been used to estimate the vascular wall shear stress, which has a key role in vascular physiology as well as the pathophysiologic mechanisms of vascular diseases. 2 Based on Poiseuille theory, the blood flow velocity profile is parabolic, and high-velocity gradients occur at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Values of BCW ranged between approximately 200 and 500 µm and increased linearly with depth even though the L12-3 probe has an elevational focal at 20 mm. Similar calibrated BCW curves have been found in other studies [21], [34]. When the depth is over 35 mm, the calibrated BCW values start to fluctuate, which is caused by the low signal-to-noise ratio (SNR) in the deeper area and the incoherence of the beam [34].…”
Section: A An Example Of a Calibrated Bcw Curve From The Speckle Phasupporting
confidence: 80%
See 2 more Smart Citations
“…Values of BCW ranged between approximately 200 and 500 µm and increased linearly with depth even though the L12-3 probe has an elevational focal at 20 mm. Similar calibrated BCW curves have been found in other studies [21], [34]. When the depth is over 35 mm, the calibrated BCW values start to fluctuate, which is caused by the low signal-to-noise ratio (SNR) in the deeper area and the incoherence of the beam [34].…”
Section: A An Example Of a Calibrated Bcw Curve From The Speckle Phasupporting
confidence: 80%
“…This study is the first to address that challenge by combining speckle decorrelation, 2D high-frame-rate plane wave ultrasound and microbubble contrast agents. Experiments in the flow phantom and the in vivo study of a rabbit aorta show not only that the new approach can accurately estimate flow but also that it substantially extends the upper limit of the measurable flow velocity, to above 1 m/s, compared to the 0.2 m/s obtained in previous studies that employed speckle decorrelation with conventional ultrasound techniques [21]. Such capability enables the technique to be used for measuring physiological flows in arteries.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Doppler and correlation-based velocity measurement cannot be used in side-looking imaging systems because the imaging plane is perpendicular to the blood flow. The decorrelation-based approach [6] can be used to measure blood velocity, but this approach requires extra calibration [25], which is difficult to perform in vivo . To enable forward-viewing capability and velocity measurement as well as to boost the frame rate of a combined IVPA and IVUS imaging system, a forward-looking transducer array can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the literature on ultrasound speckle decorrelation for flow speed measurements in medical applications, it has been found that velocity estimations are strongly dependent on the noise of the data [25,26], a point that has not been addressed in speckle OCT systematically. Interestingly, we are aware of only a recent study that approaches the issue of a thorough validation of ultrasound speckle decorrelation measurements [27].…”
Section: Introductionmentioning
confidence: 99%